2003
DOI: 10.1073/pnas.2233572100
|View full text |Cite
|
Sign up to set email alerts
|

Murine cytomegalovirus m157 mutation and variation leads to immune evasion of natural killer cells

Abstract: Effective natural killer (NK) cell recognition of murine cytomegalovirus (MCMV)-infected cells depends on binding of the Ly49H NK cell activation receptor to the m157 viral glycoprotein. Here we addressed the immunological consequences of variation in m157 sequence and function. We found that most strains of MCMV possess forms of m157 that evade Ly49H-dependent NK cell activation. Importantly, repeated passage of MCMV through resistant Ly49H ؉ mice resulted in the rapid emergence of m157 mutants that elude Ly4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
185
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(189 citation statements)
references
References 41 publications
4
185
0
Order By: Relevance
“…These results are consistent with previous studies of EBV suggesting that gammaherpesviruses can mutate immunodominant viral epitopes in response to host immune pressure. In vivo mutation of a betaherpesvirus in response to immune selection has previously been shown for murine cytomegalovirus (MCMV) recognized by Ly49H-expressing natural killer (NK) cells (9,26). The data presented here show that a similar phenomenon can occur for a gammaherpesvirus under CD8 T cell-mediated immune pressure.…”
supporting
confidence: 70%
“…These results are consistent with previous studies of EBV suggesting that gammaherpesviruses can mutate immunodominant viral epitopes in response to host immune pressure. In vivo mutation of a betaherpesvirus in response to immune selection has previously been shown for murine cytomegalovirus (MCMV) recognized by Ly49H-expressing natural killer (NK) cells (9,26). The data presented here show that a similar phenomenon can occur for a gammaherpesvirus under CD8 T cell-mediated immune pressure.…”
supporting
confidence: 70%
“…As previously reported [31][32][33], structure of virus such as mouse cytomegalovirus (MCMV) m157 may be recognized as the ligand of activating or inhibitory NK cell receptor (so called ''none-self''), by which NK cells may attack self-tissue. Until now, no report including our preliminary study (data not shown) demonstrates that HBsAg has the character.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have indicated that certain mutations in the m157 gene resulted in immune evasion of MCMV from the NK cells of infected B6 mice, which are normally resistant to such a virus (26,27). This escape ability is largely attributed to the failure of mutant m157 to engage Ly49H-activating receptors.…”
Section: Discussionmentioning
confidence: 99%